Pengembangan LKS Berbasis Etnomatematika untuk Memfasilitasi Kemampuan Representasi Matematis - Astuti, Novita; Jana, Padrul; Marsiyam, Marsiyam (Edumatica : Jurnal Pendidikan Matematika, 2022)
The mathematical representation ability of junior high school (SMP) students is still not optimal. This study aims to develop student activity sheets (LKS) with valid, practical and effective criteria based on ethnomathematics which can specifically facilitate students' mathematical representation abilities. The worksheets were developed in order to facilitate students' mathematical representation skills through pictures and symbols. This study uses research and development (R&D) methods by applying the ADDIE model, namely: analysis (analysis), design (design), development (development), implementation (implementation), and evaluation (evaluation). The LKS was tested on 32 grade 7B students of SMP N 1 Mlati for the 2020/2021 academic year. The instruments used were interview guide sheets, material expert and media expert assessment questionnaires, student and teacher response questionnaires, learning implementation observation sheets, and mathematical representation ability test questions. Based on the results of the study, it was obtained: (1) LKS was declared "valid" with an average expert score of 81.03% with very good criteria. (2) LKS is declared "practical" with the average score of the questionnaire response of educators and students to LKS is 4.2 with good criteria, and the results of observations of learning implementation obtained an average score percentage of 92.33% with very good criteria. (3) LKS is declared "effective" with the percentage of the average score of the mathematical representation ability test, which is 76.92% with good criteria. The LKS compiled meet the criteria of being valid, practical, and effective so that they can be used in learning.